THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL CLIMATE ON EMPLOYEE'S ORGANIZATIONAL COMMITMENT IN THE REGIONAL PERSONNEL AND HUMAN RESOURCES DEVELOPMENT AGENCY (BKPSDMD) MAKASSAR CITY - Rahmayani, Feby; Ramli, Anwar; Dipoatmodjo, Tenri Sayu Puspitaningsih; Hasbiah, Sitti; Kurniawan, Agung Widhi (Transpublika Publisher, 2023)
Organizational culture and organizational climate play crucial roles in shaping employee commitment. Organizational culture encompasses shared values and beliefs, while organizational climate pertains to the prevailing attitudes and feelings in the workplace. Positive culture and climate foster employee engagement, satisfaction, and commitment, while negative ones can lead to decreased commitment and increased turnover. This study aims to examines the influence of organizational culture and climate on employee commitment at BKPSDMD Makassar City. The research includes 121 employees from the Regional Employment and Human Resources Development Agency. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that organizational culture has a negative effect on employee commitment, reflected in a coefficient value of -0.272 and a t-statistic of 2.032 (t-statistic > t-table, p < 0.05). Conversely, organizational climate significantly and positively impacts employee commitment, with a coefficient value of 0.586 and a t-statistic of 6.217 (t-statistic > t-table, p < 0.05). Simultaneously, both variables collectively influence organizational commitment, as shown by an F-statistic of 91.416 (F-statistic > F-table, p < 0.05). These findings contribute to the existing literature on organizational behavior and offer practical implications for enhancing employee commitment in similar contexts.